Perbandingan Gross Profit Margin PT Mayora Indah dengan PT Nippon Indosari Corpindo - Dian Aryani; Puji Muniarty (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2020)
Comparison of Gross Profit Margin of PT. Mayora Indah Tbk with PT Nippon Indosari Corpindo Tbk. This research study to study and analyze there is no difference in the gross profit margin of PT. Mayora Indah Tbk with PT. Nippon Indosari Corpindo Tbk. This research uses comparative research. With a sample of research for 10 years from 2009-2018. Samples were taken using purposive sampling technique. The analytical method used is gross profit margin analysis and technical analysis of the data used is the Independent T Test. The results of this study indicate there is no difference between PT. Mayora Indah Tbk with PT. Nippon Indosari Corpindo.